Comparison of outcomes in neck pain patients with and without dizziness undergoing chiropractic treatment: a prospective cohort study with 6 month follow-up - Humphreys B Kim (Chiropractic & Manual Therapies, 2013)
Abstract Background The symptom ‘dizziness’ is common in patients with chronic whiplash related disorders. However, little is known about dizziness in neck pain patients who have not suffered whiplash. Therefore, the purposes of this study are to compare baseline factors and clinical outcomes of neck pain patients with and without dizziness undergoing chiropractic treatment and to compare outcomes based on gender. Methods This prospective cohort study compares adult neck pain patients with dizziness (n = 177) to neck pain patients without dizziness (n = 228) who presented for chiropractic treatment, (no chiropractic or manual therapy in the previous 3 months). Patients completed the numerical pain rating scale (NRS) and Bournemouth questionnaire (BQN) at baseline. At 1, 3 and 6 months after start of treatment the NRS and BQN were completed along with the Patient Global Impression of Change (PGIC) scale. Demographic information was also collected. Improvement at each follow-up data collection point was categorized using the PGIC as ‘improved’ or ‘not improved’. Differences between the two groups for NRS and BQN subscale and total scores were calculated using the unpaired Student’s t-test. Gender differences between the patients with dizziness were also calculated using the unpaired t-test. Results Females accounted for 75% of patients with dizziness. The majority of patients with and without dizziness reported clinically relevant improvement at 1, 3 and 6 months with 80% of patients with dizziness and 78% of patients without dizziness being improved at 6 months. Patients with dizziness reported significantly higher baseline NRS and BQN scores, but at 6 months there were no significant differences between patients with and without dizziness for any of the outcome measures. Females with dizziness reported higher levels of depression compared to males at 1, 3 and 6 months (p = 0.007, 0.005, 0.022). Conclusions Neck pain patients with dizziness reported significantly higher pain and disability scores at baseline compared to patients without dizziness. A high proportion of patients in both groups reported clinically relevant improvement on the PGIC scale. At 6 months after start of chiropractic treatment there were no differences in any outcome measures between the two groups.